Does public health insurance increase maternal health care utilization in Egypt? - Ahmed Shoukry Rashad; Mesbah Fathy Sharaf; Elhussien I. Mansour (Frankfurt School of Finance & Management, 2016)
We assess the impact of health insurance on the utilization of maternal health care services in Egypt. A propensity score matching is used to control for baseline differences in the characteristics of the insured and uninsured women, to determine the difference in health care utilization between the two groups that is attributed solely to the health insurance coverage. The results yield that the national health insurance has a strong positive impact on most of the maternal healthcare indicators. Public health insurance coverage increases the likelihood of receiving antenatal care by about 7%, delivering in a public health facility by 8%, and the likelihood that a newborn receive vitamin A dose after delivery by 8.2%. However, women who are less educated, from a poor household, and rural regions, are less likely to be covered by a health insurance. The findings of this study would guide intervention measures that aim at improving health care utilization especially among the poor and other vulnerable groups.
Keywords: I14; I15; 330; maternal care utilization; health insurance; propensity score matching; Egypt